Prevalence, epidemiology and management of canker disease caused by Xanthomonas citri pv. citri in Sargodha district of Pakistan - Sharif, Arslan; Khan, Muhammad Aslam; Atiq, Muhammad; Rajput, Nasir Ahmed; Fatima, Kiran; Arif, Ehtsaham; Qayyum, Abdul; Tariq, Hamza (Journal of Pure and Applied Agriculture, 2023)
A comprehensive survey was conducted during 2020 in district Sargodha (Sargodha, Sillan Wali, Bhalwal, Kot Momin, Sahiwal and Shahpur) in Pakistan to know the intensity of citrus canker. For this purpose, five orchards of each tehsil of district Sargodha were selected to find out the incidence of citrus canker by using a zigzag method of sampling. Data was recorded on five varieties (Grapefruit, Musambi, Kinnow, Khatti and Desi lemon) of citrus in all tehsils of district Sargodha. From each tehsil three orchards (10 plants of each citrus species from each orchard) were selected to collect data regarding incidence of canker. Maximum disease incidence was recorded in Sahiwal (52.5%) while the minimum in Kot Momin (29.722%). The maximum disease incidence was recorded on Grapefruit (60%). Environmental factors i.e. temperature (max. and mini oC), rainfall (mm), wind speed (km/h) and relative humidity (%) exhibited significant positive correlation with all varieties. Regression analysis showed that canker incidence (52.5%) was observed at maximum temperature (28-38 oC), minimum temperature (18-29 oC), relative humidity (40-88%), wind speed (5-15km/h) and rainfall (3-6mm). For management of citrus canker, Copper nitrate, Copper acetate, Streptomycin sulphate, Penicillin, C. Gigentia and Fenugreek were evaluated in lab conditions. Copper nitrate and Streptomycin were proved the most effective under laboratory conditions by expressing 33.2, 31.19 mm inhibition zone while in greenhouse and field conditions combination of copper nitrate and streptomycin sulphate expressed minimum incidence of citrus canker (13.82 and 18.44) % respectively. In case interaction between treatments and their concentration, minimum incidence of disease was expressed by combination copper nitrate and streptomycin sulphate (15.94, 13.75 11.77 and 24.41, 18.63, 12.27) % under greenhouse and field conditions, respectively. Similar observations were recorded in case of interaction between treatments and days after 7, 14 and 21 days under greenhouse and field conditions. © 2021 Department of Agricultural Sciences, AIOU